1990
DOI: 10.1272/jnms1923.57.222
|View full text |Cite
|
Sign up to set email alerts
|

Studies of cerebral blood flow and metabolism in patients with senile dementia of the Alzheimer's type and diagnostic evaluation of the dementing illnesses by positron emission tomography.

Abstract: This study was designed to estimate cerebral dysfunction in senile dementia of the Alzheimer's type (SDAT). Regional cerebral blood flow (rCBF), oxygen extraction fraction (rOEF) and cerebral oxygen consumption (rCMR02) were studied in 16 patients with SDAT and 5 age-matched normal elderly people by positron emission tomography (PET), using the 150 labeled CO2 and 02 inhalation technique.This technique was also applied to the evaluation of PET in diagnosing the dementing illnesses.In this study, a total of 19 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1994
1994
2006
2006

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Paralleling the pattern of decrease glucose uptake, PET studies have observed a decrease in H 2 15 O, and therefore CBF, in the temporal and parietal cortices [58][59][60]. Although a few studies show areas of increased perfusion in early AD, mostly in the primary cortex and dorsolateral frontal region, Fig.…”
Section: B Cerebral Blood Flowmentioning
confidence: 82%
“…Paralleling the pattern of decrease glucose uptake, PET studies have observed a decrease in H 2 15 O, and therefore CBF, in the temporal and parietal cortices [58][59][60]. Although a few studies show areas of increased perfusion in early AD, mostly in the primary cortex and dorsolateral frontal region, Fig.…”
Section: B Cerebral Blood Flowmentioning
confidence: 82%
“…Therefore, this ratio is suggested to be of benefit in differential diagnosis. The ratio reflects a hypofrontal flow pattern in FTD, which has been described in previous studies [12][13][14][15][16][17]41]. However, fewer patients were included in these studies and other methods were sometimes used, e.g.…”
Section: Discussionmentioning
confidence: 90%
“…Among the methods for semiquantification, the min-max method has been reported to involve a smaller observer error and to have bet- ter reproducibility than other more commonly used methods [11]. Investigations of rCBF in FTD, using different methods, have generally found reductions in the frontal lobes [12][13][14][15][16][17]. Such reductions are included in the proposed Lund-Manchester consensus criteria for a diagnosis of FTD [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This observation which has been widely referenced, was recently chal lenged by more sensitive PET studies which have shown that patients with Alzheimer's disease have significant increases in OEF [83,84]. Moreover, misery perfusion appears present not only in Alzheimer patients but also in other dementias [85], In one clinical case study, neurofibrillary tangles were re ported to form quickly in the nucleus basalis of Meynert following a cerebral infarction near the area of tangle accumulation [86],…”
Section: Oxygen Extraction Fractionmentioning
confidence: 96%